Online Paraphrasing Practices for Academic Writing in Indonesian Higher Education - ‎ , Fitriani; Jihad, Adriani; Alimuddin, Andi Haeriati; Bahang, M Dahlan (KnE Social Sciences, 2024)
This research aims to examine how higher education students paraphrase their academic writing to reduce high Turnitin similarity scores. The research uses a descriptive–qualitative research design. Data were collected through observations and in-depth interviews. The observation was conducted by analyzing 20 higher education students’ theses in terms of paraphrasing practices. The in-depth interviews with five selected participants were conducted by asking some questions related to the observation results about paraphrasing practices. Based on the observation and the in-depth interviews, the researcher found that most of the students prefer to do paraphrasing practices online compared to paraphrasing practices manually. In addition, most students already know the meaning of paraphrasing but some students have not applied it adequately. The researchers conclude that online paraphrasing is a great idea that can be used to simplify paraphrasing activities. However, the students need to re-read the results of the paraphrase from the online paraphrase to be analyzed and revised if needed. It is crucial to focus on the overall quality of the paraphrased results, making sure to check for proper word choice and grammar. In addition, further research is required to determine the extent to which the text’s original context and meaning have been successfully maintained. Keywords: academic writing, paraphrasing, online paraphrasing tool, Turnitin, higher education